Bioaerosols and the Indoor Air Quality of a University Library in Surat Thani Province - Chaiwiset, Suchada; Ramsri, Pitchayapa; Boriphet, Bensai; Aksornthai, Laphatrada; Thaikert, Ratchadaporn; Mala, Jirawat (YRU Journal of Science and Technology, 2025)
Indoor air quality plays a crucial role in the health and well-being of individuals working within a building. This study presents a cross-sectional descriptive investigation aimed at evaluating indoor air quality and the presence of microorganisms, as well as exploring the correlation between microorganism levels and air quality within the library building of a university in Surat Thani Province, Thailand. The study included biological measurements of indoor air pollution, specifically total bacteria and fungi, alongside assessments of chemical factors (carbon dioxide and carbon monoxide) and thermal comfort (temperature and relative humidity). A selection of sampling sites was established, and measurements were conducted over four weeks, with two consecutive days of sampling each week. The collected data underwent analysis using descriptive statistics, analysis of variance, and correlation coefficients. The findings indicated that the levels of temperature, carbon dioxide, carbon monoxide, total bacteria, and fungi within the library building fell within the acceptable limits defined by the Department of Health guidelines. However, the relative humidity ranged from 47.3 to 82.3 percent, averaging 68.5±6.5 percent, which did not meet the recommended criteria of 50-65 percent. There were no significant correlations found between bioaerosols and temperature, relative humidity, CO2, and CO levels (p>0.01). Additionally, the microbiological assessment of the library services indicated a statistically significant difference in the levels of bacteria and fungi (p< 0.05). The indoor-to-outdoor (I/O) ratios for carbon dioxide and bacteria were 1.3 and 1.2 times, respectively, indicating an inadequacy in ventilation from the inside of the building to the outside. Therefore, it is imperative for the library to enhance ventilation to lower humidity, carbon dioxide, and bacterial counts, while also ensuring ongoing monitoring and maintenance of indoor air quality.